2012
DOI: 10.1017/s0025315412001488
|View full text |Cite
|
Sign up to set email alerts
|

Comparative reproductive biology of Sciaenidae family species in the Río de la Plata and Buenos Aires Coastal Zone, Argentina

Abstract: A comparative analysis on various aspects of the reproductive biology of 7 Sciaenidae family species was done. In addition the reproductive parameters needed for stock assessment models were provided. The research covered the analysis of the duration of the breeding season and the estimation of reproductive variables such as size at maturity, fecundity and spawning frequency. When all species were considered together, some aspects of reproduction were similar, regarding the reproductive strategy; all species a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 19 publications
4
18
0
2
Order By: Relevance
“…These values are similar to that reported by Fostier et al (2000) but lower than obtained for others sparids like Sparus macrophtalamus (Nguyen-Xuan, Wojciechowski, 1973), Dentex dentex (Loir et al, 2001), Dentex gibbosus (Grubisic et al, 2007) and Diplodus vulgaris (Gonçalves, Erzini, 2000). Mean values of RF were similar to those reported for M. furnieri, C. guatucupa and Umbrina canosai (Militelli et al, 2013) and lower than those for P. brasiliensis (319 ± 129 oocytes/ g for 1999 ;Militelli, Macchi, 2001).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These values are similar to that reported by Fostier et al (2000) but lower than obtained for others sparids like Sparus macrophtalamus (Nguyen-Xuan, Wojciechowski, 1973), Dentex dentex (Loir et al, 2001), Dentex gibbosus (Grubisic et al, 2007) and Diplodus vulgaris (Gonçalves, Erzini, 2000). Mean values of RF were similar to those reported for M. furnieri, C. guatucupa and Umbrina canosai (Militelli et al, 2013) and lower than those for P. brasiliensis (319 ± 129 oocytes/ g for 1999 ;Militelli, Macchi, 2001).…”
Section: Discussionsupporting
confidence: 88%
“…In general, the size of hydrated oocytes in red porgy was similar to that found in other sparids that range 850-1090 µm (Glamuzina et al, 1989;Greco et al, 1993) and higher than Pagellus erythrinus (Güner et al, 2004). Pagrus pagrus OD and OdD were also similar to other species of BCE like M. furnieri, C. guatucupa, U. canosai (Militelli et al, 2013) and P. brasiliensis (Militelli, 1999), but the oocyte dry weight estimated for the last one was lower (1.70 ± 0.12 mg to 100 oocytes for 2003) (Rodrigues et al, 2007).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…As a general rule, fecundity in fishes decreases with increasing egg size and increasing parental care (Helfman et al, 2009). In sciaenids inhabiting the Buenos Aires Coastal Zone off Argentina, Militelli et al (2013) found support for this idea since Pogonias cromis (Linnaeus, 1766), the only species that had a smaller mean relative fecundity ranging between 75 and 98 oocytes/g, had also larger oocytes (1100-1400 µm in diameter) compared with the six remaining species studied, whose ooocyte diameters ranged between 750 and 900 µm. However, this inverse relationship between egg size and fecundity was not verified in the genera Pinguipes: P. brasilianus had higher batch and relative fecundity and larger oocytes than P. chilensis (between 700 and 1100 µm in P. brasilianus vs. <500 µm in P. chilensis, González Kother, 2001).…”
Section: Discussionmentioning
confidence: 93%
“…Relative fecundity in P. brasilianus was low compared with other South Atlantic species, like hakes (e.g., Merluccius hubbsi Marini, 1933: 85-1040 oocytes/g, for fish between 29 and 95 cm TL, Macchi et al, 2013) and sciaenids (mostly about 150-200 oocytes/g, Militelli et al, 2013). As a general rule, fecundity in fishes decreases with increasing egg size and increasing parental care (Helfman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%